Analisa Implementasi Strategi Pemasaran Untuk Meningkatkan Jumlah Pelanggan Di Waroeng Steak And Shake Cempaka Putih Jakarta Pusat - Wiwi Nurhayati; Thamrin Thamrin; Ghita Yasaningthias (JAMBIS : Jurnal Administrasi Bisnis, 2021)
Waroeng Steak and Shake is a steakhouse that stands with the concept of simplicityand the principles of Halalan Thayyiban. However, in its business activities, the Waroeng Steakand Shake menu is considered to have gradually increased and there are no bookings forevents. The purpose of this study was to analyze the implementation of the marketing strategyto increase the customers at Waroeng Steak and Shake which was reviewed through theMarketing Mix along with its obstacles and solutions. This research was conducted using adescriptive qualitative approach with observation and interview techniques. The resultsshowed that Waroeng Steak and Shake experienced an increase in July to December but alsoa decrease in the following six months in 2020, January to June. This was due to the Covid-19 Pandemic that has caused a decline or even setback in business sectors. However, the7P Marketing Mix strategy carried out by Waroeng Steak and Shake Cempaka Putih CentralJakarta actually increased the number of customers. Started from May to June 2020 thenumber of customers was stable, which means moving forward from the decline in theprevious months, considering the new normal situation with the health protocol enforced bythe government.